Rural tourism enhances smallholder farmer livelihoods [Tanzania] - Neligwa, Michael (Technical Centre for Agricultural and Rural Cooperation, 2018)
Tourists visiting rural Tanzanian communities are offering an alternative source of income to farmers. The national network of small-scale farmers' groups in Tanzania, MVIWATA, has collaborated with a travel guide organisation to provide a novel experience for guests, and boost the incomes of farmers and farmer groups in 10 rural villages, with exciting results.